Materials science and technology :a comprehensive treatment /. Volume 1, Structure of solids / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Volume editor : Volkmar Gerold - Cahn, R. W.
Vol. 1 published in 1993.